Estructura electrónica de aleación AlAs con red zincblende, calculadas con el método LMTO - Cabrera, César (2020)
The structure of energy bands, the density of states, the prohibited energy and the total energy calcu- lated using the linear mun-tin orbitals (LMTO) method in the framework of the density functional theory (DFT) in presented. The Schrödinger equation was solved with a parameterized potential in the local density approximation (LDA) with the Barh-Hedin approximation for the term of exchange correlation. The electronic structure resulted in an indirect forbidden energy gap of 2.203 eV associated with a minimum total energy of −18.10 Ry and close to the experimental data.